L’immagine scenica: dalla riproduzione specchiata del reale all’icona visionaria - Tessari, Roberto (Scenari, 2021)
At the end of the nineteenth century the model of the scenic image changed: the model is no longer painting, but photography. A new scenic illusionism is born, against which the poetic of Jarry, the conception of the light of Appia and the directorial theory of Gordon Craig take place. Thanks to these interventions, theater is no longer conceived as a mirror image of reality, but as a place for the autonomous creativity of an imaginary that goes beyond the mere reproduction of organic nature. In the early twentieth century, the postulates of the scenic frame and the fourth wall were broken: with reference to the models of the variety or the circus, with the conventionalism of Meyerhol’d, with the political theater of the Weimar republic. After these events, the theatrical image becomes a free image of positioning and flowing in the space and time in which the spectator is immersed, displaced by the conditioning of a scene that imitates the picture or the photograph, dissolved by the imperative of the verisimilitude.